The Effect Of Duration Of Diabetes Mellitus On The Incidence Of Lower Extremity Disorders - Sofyan Sofyan; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Diabetes mellitus ( DM) is chronic metabolic disease that May lead to various microvascular and macrovascular complications . One of the common complications involves the lower extremities , including diabetic peripheral neuropathy , peripheral artery disease , diabetic foot ulcers , infection , impaired wound healing , and amputation . The duration of diabetes is considered to be associated with an increased risk of these complications due to prolonged exposure to hyperglycemia and progressive nerve and vascular damage .This article aimed to analyze the influence of diabetes mellitus duration on the occurrence of lower extremity disorders based on available scientific evidence .This article used literature​ review approach by examining scientific publications and clinical guidelines addressing the relationship between diabetes duration and peripheral neuropathy , peripheral artery disease , diabetic foot ulcers , and lower extremity complications .A longer duration of diabetes is generally associated with an increased risk of lower extremity disorders . Prolonged exposure to hyperglycemia May contribute to peripheral nerve damage , microvascular dysfunction , atherosclerosis , and impaired tissue perfusion . Neuropathy causes loss of protective sensation , allowing foot injuries to remain unnoticed , while peripheral artery disease impairs wound healing . The combination of neuropathy , impaired perfusion , foot deformity , and infection May increase the risk of ulceration and amputation . However , diabetes duration is not the only determinant , as glycemic control , age , hypertension , dyslipidemia , smoking , obesity , chronic kidney disease , and a history of ulceration or amputation also contribute . The longer a person has diabetes, the greater the potential risk of lower extremity complications , particularly when risk factors are poorly controlled and foot examinations are inadequate . Early detection and continuous preventive management are essential .